An insulinoma presenting with hypochondriac delusions and food refusal - Renca, S (2013)
ABSTRACT The authors report a case of a 68-year-old man with an unrecognized insulinoma manifesting with neuropsychiatric symptoms. For two years, he presented with unspecified behavior changes, autonomic and neuroglycopenic symptoms, which led him to be misdiagnosed with a neurologic and psychiatric disorder before the insulinoma was recognized. Following neurological alterations in context of hypoglycemia, subsequent to longstanding food refusal, he was admitted in the psychiatric ward. Despite good global response and normal food intake, hypoglycemic episodes were still occurring and led to a careful evaluation which permitted the definitive diagnostic. This case highlights the diagnostic difficulties of medical disorders presenting with clinical features overlapping neurological and psychiatric syndromes. It also reflects the diagnostic difficulties in rare clinical entities, particularly in patients previously followed in psychiatry and underlines the need for a constant dialogue and updating of clinicians.